Analysis of Characteristics for Cyclic Business Processes - Tarumyan, Lusine S. (Mathematical Problems of Computer Science, 2021)
A new method for evaluation of business process characteristics is proposed, which is applicable at design stage when probabilities of process transitions are unknown. Among a variety of publications on the process analysis, only a few address processes under unknown probabilities of transitions. The latter consider only acyclic processes, which restricts their application scope. The suggested method is based on a transformation of unstructured cycles into LOOP cycles. It gives an opportunity to represent a process via a hierarchy of LOOPs and to apply dynamic programming methodology for characteristics analysis. It allows to extend the algorithms, initially developed for acyclic processes, for the analysis of cyclic processes, preserving at the same time the polynomial complexity of source algorithms. The introduced method has been used to develop effective algorithms for determination of the main characteristics of a business process (including time, cost, revenue, and profit).